Preparation and Characterization of Amylose Inclusion Complexes for Drug Delivery Applications - Carbinatto, Fernanda M. [UNESP]; Ribeiro, Tatiana S.; Colnago, Luiz Alberto; Evangelista, Raul Cesar [UNESP]; Cury, Beatriz S. F. [UNESP] (Wiley-Blackwell, 2016)
Amylose complexes with nimesulide (NMS) and praziquantel (PZQ) were prepared by a simple and low cost method, so that high yield (>57%) and drug content (up to 68.16%) were achieved. The influence of drug: polymer ratio, temperature, and presence of palmitic acid on the complexes properties was evaluated. Differential scanning calorimetry, X-ray diffraction, and nuclear magnetic resonance data evidenced the drug-polymer interaction and the formation of inclusion complexes with semi-crystalline structures related to type II complexes. The drug release rates from complexes were lowered in acid media (pH 1.2) and phosphate buffer (pH 6.9). The presence of pancreatin promoted a significant acceleration of the release rates of both drugs, evidencing the enzymatic degradability of these complexes. The highest enzymatic resistance of PZQ1:30PA60 degrees C complex makes the release time longer and the full release of PZQ in phosphate buffer with pancreatin occurred at 240 min, whereas the complexes with NMS and PZQ1:5PA90 degrees C did it in 60 min. According to the Weibull model, the drug release process in media without enzyme occurred by complex mechanisms involving diffusion, swelling, and erosion. In media containing pancreatin, generally, the better correlation was with the first order, evidencing the acceleration of the release rates of drugs in the early stages of the test, due to enzymatic degradation. (C) 2016 American Pharmacists Association (R). Published by Elsevier Inc. All rights reserved.
Keywords: inclusion complexes; high amylose; nimesulide; praziquantel; controlled release; solid state NMR; X-ray diffractometry; calorimetry (DSC); dissolution